Slurry application techniques to reduce ammonia emissions: Results of some UK field-scale experiments - MISSELBROOK, T. H; SMITH, K. A; JOHNSON, R. A; PAIN, B. F (Biosystems engineering, 2002)
Shallow injection, trailing shoe and band spreading machines were evaluated, in terms of their potential for reducing ammonia (NH3) emission, by making measurements after application and in direct comparison with surface broadcast applied cattle slurry (pig slurry on one occasion). Several sets of comparative measurements were made with each type of machine on both grassland and arable land (mostly cereal stubbles), covering a range of soil, crop and weather conditions. Measurements of NH3 emissions were made for 5-7 days following application using a micrometeorological mass balance technique. Mean reductions in NH3 emission achieved from grassland, in comparison with surface broadcast application, were 73, 57 and 26% for shallow injection, trailing shoe and band spreading, respectively, the latter not being significant (probability P > 0.05). Mean cumulative emissions, expressed as % total ammoniacal N applied in the slurry, were 13, 12 and 35% for shallow injection, trailing shoe and band spreading, respectively. There was a trend (probability P = 0.029) for decreasing emissions with increasing sward height (between 10 and 20 cm) following trailing shoe applications. Abatement was generally less effective when these techniques were used on arable land, with mean reductions of 23, 38 and 27% achieved for shallow injection, trailing shoe and band spreading, respectively, with none achieving statistical significance (probability P > 0.05). There was considerable variation in the efficiency of shallow injection, with reductions achieved in individual experiments ranging from 0 to 90%. The considerable variability in efficiency of the techniques for NH3 emission abatement warrants further investigation.